Axiology of Payables And Receivables In The Perspective of Sharia Finance Accounting - Luthfia, Nadira; Purbaningrum, Ivana Rosa; Nasim, Arim; Suryadi, Edi (Journal Analytica Islamica, 2024)
Axiology in the context of financial accounting for debt and receivables transactions involves the application of ethical principles, moral values, and philosophical values in the management and reporting of debt and receivables. In the Islamic perspective, the axiology of financial accounting for debt and receivables becomes a profound study by applying Sharia principles as the main guidance. One of the fundamental principles that serves as a foundation is the prohibition of usury (riba). This research employs a qualitative research method in the form of a literature review with a systematic reviews approach. The data used in this research refer to books and research articles. Data search is conducted using keywords such as "Axiology of Debt and Receivables in the Philosophy Perspective, Debt and Receivables in Islam." The practice of debt and receivables is regulated in Sharia to assist those facing difficulties and provide assistance to those in need. However, the presence of usury can undermine the good intentions behind this assistance, as those facing difficulties must pay additional money from their borrowings. Axiologically, debt and receivables involving usury are considered undesirable.Aksiologi dalam konteks akuntansi keuangan pada transaksi utang piutang melibatkan penerapan prinsip-prinsip etika, moral, dan nilai-nilai filosofis dalam pengelolaan dan pelaporan utang piutang. Dalam perspektif Islam, aksiologi akuntansi keuangan utang piutang menjadi kajian yang mendalam dengan menerapkan prinsip-prinsip syariah sebagai pedoman utama. Salah satu prinsip utama yang menjadi pijakan adalah larangan riba. Penelitian ini menggunakan metode penelitian kualitatif dalam bentuk literature review dengan pendekatan systematic reviews. Data yang digunakan dalam penelitian ini merujuk pada buku dan artikel penelitian. Pencarian data dilakukan dengan menggunakan kata kunci, seperti “Aksiologi Utang Piutang Utang Piutang dalam Perspektif Filsafat Aksiologi Utang Piutang dalam Islam”. Praktek utang piutang diatur dalam syariat untuk membantu menyelamatkan orang-orang yang mengalami kesulitan dan memberikan bantuan kepada mereka yang membutuhkan. Namun, keberadaan riba dapat menghilangkan niat baik dalam tolong-menolong ini karena pihak yang mengalami kesulitan harus membayar tambahan uang dari pinjamannya. Secara aksiologis pun, utang piutang yang melibatkan riba di dalamnya dinilai tidak baik.